Perwujudan Manajerial dan Kepemimpinan dalam Ekstrakurikuler Seni di Sekolah - Putra Andino Nugrahhu; Aldia Wulandari (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
One of the most popular school organizations is the student council. But in reality, the student council also has limitations to embrace all the large number of students in the school. Therefore, other organizations are needed that can be a place for students, especially with kinesthetic intelligence, to develop and self-actualize. This paper aims to open the insight that extracurricular dance can be a place for students' leadership training. How the cultivation of leadership values in extracurricular dance and implementation in schools is the core that will be discussed. The result is that leadership characteristics such as: honest, knowledgeable, courage to make decisions, trustworthy, initiative, wish, firm, fair, exemplary, resilient, loyalty, unselfish, enthusiastic, and humble can be developed in extracurricular dance. The implementation of leadership in extracurricular dance is reflected in the tasks carried out in its simple organizational structure, namely the chairman, deputy, secretary, choreography section, fashion makeup section, music and accompaniment section, performance section, public relations section, to members.